2021
DOI: 10.1177/08901171211062800
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Implementation Science, Community-Engaged Research, and Health Promotion to Address Cancer Inequities in Massachusetts: The UMB/DF-HCC U54 Outreach Core

Abstract: The Outreach Core of the U54 Partnership between the Dana-Farber/Harvard Cancer Center and the University of Massachusetts Boston created a new model for addressing cancer inequities that integrates implementation science, community-engaged research, and health promotion. Key elements of the approach include engaging a Community Advisory Board, supporting students from underrepresented minority backgrounds to conduct health promotion and community-engaged research, increasing the delivery of evidence-based can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The 5Ws is also adaptable to all types of mixed method data collection and analysis to operationalize the 5Ws framework and provide the insights necessary to plan, implement, and share impactful community-based health research. As a result, the 5Ws framework can be an effective tool in community-engaged HIV research with Black cisgender women and youth in the US South and contributing to emerging community-engaged research in the study of dissemination and implementation science (Khazanie et al, 2022; Ramanadhan et al, 2022; Schlechter et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The 5Ws is also adaptable to all types of mixed method data collection and analysis to operationalize the 5Ws framework and provide the insights necessary to plan, implement, and share impactful community-based health research. As a result, the 5Ws framework can be an effective tool in community-engaged HIV research with Black cisgender women and youth in the US South and contributing to emerging community-engaged research in the study of dissemination and implementation science (Khazanie et al, 2022; Ramanadhan et al, 2022; Schlechter et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to go beyond traditional definitions of sustainability, to expand the construct to include more diverse voices and perspectives to advance understanding of what is needed to maximize the long-term delivery and benefits of EBIs among under-resourced communities. For any implementation effort, including but not limited to sustainability, a focus on health equity should center and uplift community values (25)(26)(27). Efforts to sustain EBIs should take into consideration the transformative nature of community engagement and its strong potential to lead toward social justice, particularly when involving the redistribution of power, resources, and decision-making (28,29).…”
Section: Challenges and Considerations In Promoting Sustainability An...mentioning
confidence: 99%
“…This is evidenced by an increasing number of perspective pieces and commentaries highlighting the potential bene ts of this integration to both research and practice, outlining examples of federal efforts to support this research, and offering of potential frameworks to accomplish that integration (9-13). There have also been a few published case studies documenting interventions that worked to integrate engagement in D&I research for a diverse range of health and related outcomes including violence, heart disease, and cancer (14)(15)(16). It is suggested that this integration of engagement methods and approaches into D&I research can lead to improved health outcomes, but this has yet to be documented in most cases (17).…”
mentioning
confidence: 99%